Phonemic awareness as an indicator of preliteral abilities in serbian speaking children with and without specific language impairment - Neda R. Milošević; Mile G. Vuković; Ivana D. Ristić (University of Belgrade, Teacher Education Faculty, 2022)
This study is based on theoretical and empirical understanding of phonemic awareness in Serbian speaking children with and without specific language impairment (SLI). The aim of this paper is to compare the phonemic awareness in children with SLI and children with typical language development (TLD) who are between 5.11 and 7 years of age. This study included 40 participants with SLI and 80 participants with TLD. The subtest for evaluation of phonemic awareness from The Test for Evaluating Reading and Writing Pre-Skills - PredČiP (Kuvač Kraljević & Lenček, 2012) was used. Statistically significant differences were confirmed on both tasks of phonemic awareness (p < .001). The half of children of the SLI group had borderline or poor achievement, generally lower than children with TLD. Bearing in mind that Serbian language has a regular orthography and clear morphological specificities, compared to most world languages, it is expected that Serbian-speaking children would master phonological awareness tasks more easily. Consequently, we believe that an early detection of phonological disorders is particularly important for the Serbian-speaking children. Having in mind that literature data indicate that children who, prior to starting school, are diagnosed with SLI, later encounter interference with reading and writing, we suggest the implementation of a analspecific preventive program for developing phonological skills, or training of phonemic awareness, in all children.